2018
DOI: 10.1016/j.aju.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of silodosin on the outcome of semi-rigid ureteroscopy for the management of large distal ureteric stones: blinded randomised trial

Abstract: ObjectiveTo evaluate the efficacy of silodosin therapy, as a new α-adrenergic receptor (α-AR) blocker, on the success rate of semi-rigid ureteroscopy (URS) for the management of large distal ureteric stones.Patients and methodsThis prospective study recruited 127 adult patients with single distal ureteric stone of ≥1 cm. The patients were randomly allocated to two groups: the first group included 62 patients who received silodosin (8 mg) for 10 days before URS (Silodosin group), whilst the second group include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 28 publications
6
32
2
Order By: Relevance
“…They found a statistically significant decrease in the need for ureteric dilatation during URS and operative time. These results were confirmed in another study by Mohey et al in 2018 [ 8 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…They found a statistically significant decrease in the need for ureteric dilatation during URS and operative time. These results were confirmed in another study by Mohey et al in 2018 [ 8 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, in 2017, Sokhal et al reported that there was not a statistically significant decrease in the need for ureteric dilatation during URS when using pre-URS tamsulosin. This may be attributed to the short-term use of pre-operative tamsulosin – for 3 days only [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the inclusion and exclusion criteria, five RCTs involving 557 patients (274 in the alpha-blockers group and 283 in the placebo group) were included in the analysis. [13][14][15][16][17] The characteristics of the individual studies are presented in Table 1. All five studies included in the meta-analysis were RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…All five studies (n ¼ 557; 274 in the alphablockers group and 283 in the placebo group) were used in the analysis of operation time. [13][14][15][16][17] Heterogeneity was found among the trials (I 2 ¼ 82%; P ¼ 0.0002), so a random-effects model was chosen for the analysis. There was no significant difference in operation time between the adjunctive alpha-blockers and placebo groups (MD: -3.33; 95% CI -7.03, 0.37; P ¼ 0.08) (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation